2020
DOI: 10.20546/ijcmas.2020.902.201
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Haemato-biochemical and Oxidative Stress Parameters in Dogs Affected with Gastroenteritis

Abstract: Gastroenteritis which is a common illness affecting all species of animals is much more severe in monogastric animals especially in dogs. The patho-physiology of gastroenteritis is quite diverse depending upon the specific etiology. The causes of gastroenteritis may be dietary, viral, bacterial, rickettsial, parasitic and miscellaneous. Gastroenteritis is characterized by varied clinical signs such as diarrhoea, vomition with or without blood, inappetance, lethargy, fever, anaemia and dehydration (Banja et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…By the end of treatment, the mean value increased to 3537.07 ± 177.13U/L of plasma, which was significantly higher compared to the enzyme activity before treatment. Kataria et al (2020a) also reported reduced GSH-Px activity in diarrhoeic animals. Ighodaro and Akinloye (2018) described that the free radicals produced as a result of oxidative damage of lipids, proteins, RNA and DNA was neutralised by antioxidant enzyme glutathione peroxidase.…”
Section: Glutathione Peroxidase Levelmentioning
confidence: 90%
“…By the end of treatment, the mean value increased to 3537.07 ± 177.13U/L of plasma, which was significantly higher compared to the enzyme activity before treatment. Kataria et al (2020a) also reported reduced GSH-Px activity in diarrhoeic animals. Ighodaro and Akinloye (2018) described that the free radicals produced as a result of oxidative damage of lipids, proteins, RNA and DNA was neutralised by antioxidant enzyme glutathione peroxidase.…”
Section: Glutathione Peroxidase Levelmentioning
confidence: 90%